2019
DOI: 10.1002/jsfa.9630
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat‐ and freeze‐drying treatments on phytochemical content and fatty acid profile of alfalfa and flax sprouts

Abstract: BACKGROUND Fresh sprouts are healthy foods, low in fats and high in phytochemicals, but have a short shelf‐life, hence the need for processing methods that preserve their nutritional value. This work was aimed at evaluating the effect of heat‐drying (HD) and freeze‐drying (FD) on the phytochemical and fatty acid profiles of alfalfa and flax sprouts, as compared to fresh material. RESULTS Both FD and HD reduced the phytochemical contents compared to fresh sprouts. FD better preserved phytoestrogens, phytosterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…As regards supplementation levels, since high amounts of fresh sprouts might reduce feed consumption and energy intake, studies are needed to evaluate their use in the form of dried powder or pellet. Mattioli et al [173] demonstrated that drying, in particular freeze-drying, did not compromise the bioactive compound contents of alfalfa and flax sprouts, and considered this evidence as promising for future research on the effect of different levels of supplementation.…”
Section: Sprouts In Animal Feedingmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards supplementation levels, since high amounts of fresh sprouts might reduce feed consumption and energy intake, studies are needed to evaluate their use in the form of dried powder or pellet. Mattioli et al [173] demonstrated that drying, in particular freeze-drying, did not compromise the bioactive compound contents of alfalfa and flax sprouts, and considered this evidence as promising for future research on the effect of different levels of supplementation.…”
Section: Sprouts In Animal Feedingmentioning
confidence: 99%
“…For example, in broccoli sprouts the highest efficiency of grinding as well as the higher total phenolic content and antioxidant activity were obtained from freeze-dried (frozen and lyophilized at 40 • C; 52 Pa) materials, although air-dried at 40 • C (air flowing, 0.5 ms −1 ) could be also recommended [172]. In alfalfa and flax sprouts, freeze-drying minimized the chemical alteration of the product, resulting in a better preservation of antioxidants and an increase in phytosterol availability [173]. Conversely, air drying at 70 and 80 • C for 24 h, as opposed to freeze drying (below −50 • C and 0.3 mbar vacuum pressure, 36 h), increased total phenolic content and antioxidant capacity of mung bean sprouts [174].…”
Section: Post-harvest Shelf Life and Processingmentioning
confidence: 99%
“…Złotek et al [21] found that drying temperature up to 45 • C has no significant influence on TPC and AC in extracts obtained from quinoa sprouts. Mattioli et al [20] revealed, that that lyophilization better maintains the content of bioactive compounds compared to air-drying. On the other hand, Gan et al [59] found that hot air-drying (at 70 and 80 • C) increased TPC and AA in mung bean sprouts in comparison to freeze-dried sprouts.…”
Section: Tpc and Acmentioning
confidence: 99%
“…The quality of dried sprouts is determined based on drying conditions and methods. In particular, conditions of sprouts drying must be chosen to preserve bioactive compounds and their nutritive value [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Esta planta cuenta con excelentes características de valor nutritivo, su consumo se da de muy diversas formas en la alimentación de humanos y ganado (Zaragoza et al, 2019). Una forma de alimentación para ganado explorada recientemente es en forma de brotes o germinados (Mattioli et al, 2019). Se ha explorado que la calidad de brotes puede ser mejorada por la incorporación de nutrimentos durante su crecimiento.…”
Section: Introductionunclassified